INTEGRATING TIKTOK VIDEO BLOGGING AS A MEDIA TO ENHANCE SPEAKING SKILLS AT MAN 4 NORTH ACEH - Hanum, Maulida; Zuraini, Zuraini; Nofriati, Eli (Journal of English Education and Social Science, 2025)
Abstract This study aims to investigate the effectiveness of TikTok video blogging in enhancing students' speaking skills. The research was conducted using Collaborative Classroom Action Research (CCAR), which allows researchers and teachers to work together to improve learning practices. The data sources for this study were 16 students from class 2 IPA 2 at MAN 4 Aceh Utara. Data collection techniques included speaking skills tests, observation sheets to assess teacher and student performance, and questionnaires to measure student responses. The research was carried out in two cycles, with each cycle consisting of planning, implementation, observation, and reflection. The results showed significant improvements in several aspects. Based on the observation checklist results, the teacher's performance in the speaking learning process using TikTok video blogging increased from 80.00% in Cycle I to 99.00% in Cycle II, indicating improved teaching effectiveness. Moreover, students' performance also improved, from 81.21% in Cycle I to 99.39% in Cycle II, suggesting higher student participation and engagement. In terms of students' speaking skills, there was a significant improvement through the use of TikTok video blogging. This can be seen from the mean score of Cycle I, which was 72.18, increasing to 81.87 in Cycle II. This improvement demonstrates that using TikTok as a learning tool can effectively help students develop their speaking skills. Finally, the questionnaire results revealed that students responded positively to the speaking learning process using TikTok video blogging, with a mean score of 2.96, placing it in the “Agree” category. These findings indicate that using popular social media platforms like TikTok can enhance student motivation and engagement in language learning. In conclusion, this research demonstrates the potential of TikTok video blogging as an effective pedagogical tool for improving students' speaking skills in the context of language learning.